Ensemble of Deep Masked Language Models for Effective Named Entity Recognition in Health and Life Science Corpora - Naderi, Nona; Knafou, Julien; Copara, Jenny; Ruch, Patrick; Teodoro, Douglas (Frontiers in Research Metrics and Analytics, 2021)
The health and life science domains are well known for their wealth of named entities found in large free text corpora, such as scientific literature and electronic health records. To unlock the value of such corpora, named entity recognition (NER) methods are proposed. Inspired by the success transformer-based pre-trained models for NER, we assess how individual and ensemble of deep masked language models perform across corpora of different health and life science domains - biology, chemistry and medicine - available in different languages - English and French. Individual deep masked language models, pre-trained on external corpora, are fined-tuned on task-specific domain and language corpora and ensembled using classical majority voting strategies. Experiments show statistically significant improvement of the ensemble models over an individual BERT-based baseline model, with an overall best performance of 77% macro F1-score. We further perform a detailed analysis of the ensemble results and show how their effectiveness changes according to entity properties, such as length, corpus frequency, and annotation consistency. The results suggest that the ensembles of deep masked language models are an effective strategy for tackling NER across corpora from the health and life science domains.